(untitled) (Swiss Medical Weekly, 2025)
AIMS: Cardiac amyloidosis (CA) characterised by myocardial amyloid accumulation is likely underdiagnosed. The distribution and extent of myocardial amyloid deposits remain unclear. With the emergence of disease-modifying drugs for ATTR and AL amyloidoses, early detection has become increasingly important. We aim to determine the frequency, clinical relevance and distribution of amyloid subtypes in cardiac amyloidosis in an autopsy cohort. METHODS: We retrospectively analysed consecutive unselected adult autopsies with cardiac amyloidosis over 10 years (January 2014 – December 2023). Two pathologists applied a biventricular semi-quantitative scoring system for interstitial and vascular amyloid deposits. Histopathological findings were correlated with ante mortem clinical data. RESULTS: Cardiac amyloidosis was found in 104 of 1972 autopsies (5%) with 91% neither diagnosed nor suspected ante mortem based on documentation in digital medical records. Ninety-eight patients (94%) had amyloid transthyretin-cardiac amyloidosis (ATTR-CA) and six (6%) amyloid light chain-cardiac amyloidosis (AL-CA). AL-CA patients were younger than ATTR-CA patients (mean ± SD: 73.2 ± 15.3 vs 84.2 ± 8.1, p = 0.006) and systemic amyloidosis was more frequent (100% vs 38%, p = 0.003). Female patients (40.4%) were significantly older (mean ± SD: 85.8 ± 8.1 years) than males (82.0 ± 9.2 years, p = 0.23), and male sex was associated with clinical suspicion and diagnosis (88.9% in males vs 11.1% in females, p = 0.06). A high vascular amyloid score correlated with systemic amyloidosis (left ventricle, p = 0.003; right ventricle, p = 0.013). Right ventricular amyloid burden was strongly linked to clinical suspicion and detection (p = 0.001). CONCLUSIONS: Our autopsy analysis found that most cardiac amyloidosis cases were undiagnosed ante mortem, especially ATTR-CA in older patients with less systemic involvement. Underdiagnosis was more pronounced in females. Our findings suggest that high vascular amyloid burden contributes to systemic amyloidosis and links right ventricular amyloid to clinical suspicion and detection.